Muslim and Buddhist encounters : between conflict and harmony - Jaffary Awang,; Ahmad Faizuddin Ramli,; Zaizul Ab Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Recent public concern over Muslim–Buddhist relations in South and Southeast Asia has emerged because of massive violence against Muslim minority groups in the region’s Buddhist-majority states. The Buddhist have expressed fear that the rise in the Muslim population would force out the Buddhists, as has happened in several historical records. Thus, in this article, we provide a preliminary analysis of Buddhist-Muslim relations from past to present as it unfolds the various forms of relations, conflicts, and harmonies. This article also analyses the driving factors that contribute to the relation of both religious societies in terms of politics, religion, and economics. This research is qualitative. The research method used is descriptive-analytical by emphasizing content analysis of data information from various books and articles covering the Muslim and Buddhism encounters. Despite certain polemics having occurred along the relationship, the study shows that Muslim-Buddhist encounter occurred in harmony, particularly when relation was rooted in tolerance. Studies affirm that disputed facts ought to be critically updated to establish the causes, which will also help address the misunderstanding between religious societies.